2011
DOI: 10.1007/s00520-011-1214-9
|View full text |Cite
|
Sign up to set email alerts
|

Unmet supportive care needs in colorectal cancer: differences by age

Abstract: While older patients reported lower levels of unmet need than younger patients, the high prevalence of unmet needs and age differences in item response patterns indicate that further research is needed to determine whether older patients' needs are being accurately captured.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
47
2
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(60 citation statements)
references
References 36 publications
6
47
2
5
Order By: Relevance
“…The median age of patients in the latter study was 74. The authors reported that younger patients had significantly greater unmet needs; however, the unmet needs of older patients appeared to be more persistent over time 32 . The increased unmet needs in the younger patients could be related to their own higher expectations to continue performing various tasks, including employment.…”
Section: Discussionmentioning
confidence: 96%
“…The median age of patients in the latter study was 74. The authors reported that younger patients had significantly greater unmet needs; however, the unmet needs of older patients appeared to be more persistent over time 32 . The increased unmet needs in the younger patients could be related to their own higher expectations to continue performing various tasks, including employment.…”
Section: Discussionmentioning
confidence: 96%
“…In an extensive review of the literature, few studies reported that cancer patients have low needs;[1019] and most studies highlight that cancer patients in both non-Western[1718192021] and Western countries[91428] have many supportive care needs. No studies identified reported such high levels of needs as reported by the participants of our study.…”
Section: Discussionmentioning
confidence: 99%
“…This means that an increasing number 6 of people may now live beyond CRC, but still experience the impact of illness and treatment on several 7 aspects of their lives (Alacacioglu et al, 2010;Arndt et al, 2004;Wu and Snyder, 2011). The need to 8 provide on-going and comprehensive supportive care to these individuals is therefore prominent 9 (Jorgensen et al, 2012). 10…”
Section: Abstract 40mentioning
confidence: 99%